2021
DOI: 10.1007/s40615-021-01078-5
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment Strategies Used in a Survey of African Immigrant Maternal Mental Health in Alberta, Canada

Abstract: African immigrant women are underrepresented in health research on maternal mental health. Thus, there is a need to highlight successful recruitment strategies to engage African women in health-oriented research. This paper offers insights on recruitment strategies utilized in recruiting African immigrant women in Alberta (Canada) with infants 2 years of age or under for a survey study on maternal mental health. We recruited 136 African immigrant women. Most participants were recruited by using already establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This cross-sectional study was conducted from January 2020 to December 2020 in Alberta, Canada. Detailed recruitment strategies for this study are given elsewhere [ 35 ]. We recruited 120 African immigrant mothers aged ≥18 years, with infants aged ≤2 years.…”
Section: Methodsmentioning
confidence: 99%
“…This cross-sectional study was conducted from January 2020 to December 2020 in Alberta, Canada. Detailed recruitment strategies for this study are given elsewhere [ 35 ]. We recruited 120 African immigrant mothers aged ≥18 years, with infants aged ≤2 years.…”
Section: Methodsmentioning
confidence: 99%
“…In both instances, informed consent was obtained prior to accessing the questionnaire. Detailed recruitment strategies for this study are given elsewhere [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Dementia research with communities such as African immigrants is limited because historically these communities have faced many social and cultural barriers to their participation and inclusion in research [ 34 ]. African immigrants reported that the following challenges limited participation in research: fear or stigma surrounding mental health or cancer [ 35 , 36 , 37 ], uncertainty/fear surrounding how data will be used [ 37 , 38 , 39 ], lack of time [ 39 ], and differential beliefs/perceptions about diseases [ 38 ]. Nevertheless, in a small sample (N = 34) of African immigrants, 91% reported a somewhat/very favorable attitude toward medical research and that medical research is important towards improving health outcomes [ 38 ].…”
Section: Introductionmentioning
confidence: 99%